NMDA receptor activation-responsive phosphoproteins in the developing optic tectum - Scheetz, AJ (J Neurosci, 1996)
A front phosphorylation assay followed by two-dimensional gel electrophoresis was used to detect proteins in the tadpole optic tectum, the phosphorylation state of which is regulated by NMDA receptor activation. Five proteins with isoelectric points between 4 and 7 displayed marked increases in their phosphorylation state in response to application of 10 microM glutamate and 50 microM NMDA. This response was inhibited by 60 microM 2-amino-5-phosphopentanoic acid. These proteins are termed NMDA receptor activation-responsive phosphoproteins (NARPPs). Two NARPPs were identified as both in vitro and in vivo substrates for protein kinase C. Of these two NARPPs, one was located in the postsynaptic density (NARPP-50), and one was located in the nuclear fraction (NARPP-21). Phosphorylation of NARPP-21 was also induced by application of the metabotropic glutamate receptor agonist trans-(+/-)-1-amino-1,3-cyclopentanedicarboxylic acid (trans- ACPD) (100 microM). Phosphorylation of all NARPPs was eliminated by dantrolene, which inhibits release of calcium from intracellular stores. In adult tecta, only NARPP-21 and -50 were phosphorylation. Thus the phosphorylation state of most NARPPs is regulated differently when synaptic plasticity is low. Further characterization of NARPPs should lead to identification of second messenger systems involved in NMDA receptor signaling and developmental synaptic plasticity.